Effect of Tetraphenylborate on Physicochemical Properties of Bovine Serum Albumin - Ola Grabowska (MDPI AG, 2021)
The binding interactions of bovine serum albumin (BSA) with tetraphenylborate ions ([B(Ph)4]−) have been investigated by a set of experimental methods (isothermal titration calorimetry, steady-state fluorescence spectroscopy, differential scanning calorimetry and circular dichroism spectroscopy) and molecular dynamics-based computational approaches. Two sets of structurally distinctive binding sites in BSA were found under the experimental conditions (10 mM cacodylate buffer, pH 7, 298.15 K). The obtained results, supported by the competitive interactions experiments of SDS with [B(Ph)4]− for BSA, enabled us to find the potential binding sites in BSA. The first site is located in the subdomain I A of the protein and binds two [B(Ph)4]− ions (logK(ITC)1 = 7.09 ± 0.10; ΔG(ITC)1 = −9.67 ± 0.14 kcal mol−1; ΔH(ITC)1 = −3.14 ± 0.12 kcal mol−1; TΔS(ITC)1 = −6.53 kcal mol−1), whereas the second site is localized in the subdomain III A and binds five ions (logK(ITC)2 = 5.39 ± 0.06; ΔG(ITC)2 = −7.35 ± 0.09 kcal mol−1; ΔH(ITC)2 = 4.00 ± 0.14 kcal mol−1; TΔS(ITC)2 = 11.3 kcal mol−1). The formation of the {[B(Ph)4]−}–BSA complex results in an increase in the thermal stability of the alfa-helical content, correlating with the saturation of the particular BSA binding sites, thus hindering its thermal unfolding.